Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1021/np960352c
|View full text |Cite
|
Sign up to set email alerts
|

Lycaconitine Revisited:  Partial Synthesis and Neuronal Nicotinic Acetylcholine Receptor Affinities

Abstract: The norditerpenoid alkaloid lycaconitine (2) was synthesized from lycoctonine (3) and its affinity determined for two neuronal nicotinic acetylcholine receptor subtypes. The structure of 2 was confirmed by a combination of spectroscopic methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…The Thus on the basis of above spectral data, the structure of compound 1 was deduced as heterophyllinine-A. Heterophyllinine-B (2), was obtained as a white amorphous powder, and was assigned the molecular formula C 24 H 35 NO 4 , on the basis of EI-MS (M þ m/z ¼ 401), and NMR spectral data. The 1 H-and 13 C-NMR spectra of heterophyllinine-B (2) exhibited a close resemblance to that of the known compound isoatisine [20,21] Thus on the basis of above spectral data, the structure of compound 2 was deduced as heterophyllinine-B.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Thus on the basis of above spectral data, the structure of compound 1 was deduced as heterophyllinine-A. Heterophyllinine-B (2), was obtained as a white amorphous powder, and was assigned the molecular formula C 24 H 35 NO 4 , on the basis of EI-MS (M þ m/z ¼ 401), and NMR spectral data. The 1 H-and 13 C-NMR spectra of heterophyllinine-B (2) exhibited a close resemblance to that of the known compound isoatisine [20,21] Thus on the basis of above spectral data, the structure of compound 2 was deduced as heterophyllinine-B.…”
Section: Resultsmentioning
confidence: 99%
“…Some aconitine and mesaconitine derivatives possess potent analgesic and anti-inflammatory activities [3]. The methyllycaconitine and lycaconitine exhibited neuronal nicotinic acetylcholine receptor affinity [4]. Lycaconitine, obtained from several Aconitum species, was found to be effective against multi-drug resistant cancers.…”
Section: Introductionmentioning
confidence: 99%
“…No radioactive agonist for α 7 receptors is available. The structurally related alkaloids elatine and nudicauline, both of which contain the methyl succinimidobenzoate moiety of methyllaconitine, had as great an affinity for α 7 receptors as methyllyaconitine (Hardick et al, 1996), while lycaconitine, which lacks only the methyl of the succimidobenzoate moiety had a 20-fold lower affinity (Jacyno et al, 1996). Simpler analogs of methyllycaconitine have been synthesized, but they had lost activity at α 7 receptors, being converted to noncompetitive blockers of α 3 β 4 receptors (Bryant et al, 2002;Ismail and Bergmeier, 2002).…”
Section: Competitive Antagonistsmentioning
confidence: 99%
“…Jacyno et al 31 reported a synthesis of lycaconitine (9) from lycoctonine (5) using only a single step to incorporate the succinimido anthranilate, in contrast to the twostep procedure utilised by Blagborough and co-workers. Anthranilic acid (14) and succinic anhydride were condensed in hot chloroform to afford the ring-opened amidodiacid 15a (Scheme 2), which was then cyclised with triethylamine in toluene to form the imide 15b.…”
Section: Semi-syntheses Of Delphinium Alkaloidsmentioning
confidence: 99%